Lattice Dynamics of Gd1−xYxMn2O5 Investigated by Infrared Spectroscopy - Javed Ahmad; Jawaria Mansoor; Mehr Khalid Rehmani; M. Tufiq Jamil; Syed Hamad Bukhari (Advances in Materials Science and Engineering)
We present infrared (IR) reflectivity of Gd1-xYxMn2O5 with x = 0, 0.2, 0.4, 0.6, 0.8, and 1 in the frequency range 30–1000 cm−1. A total of 18 IR active phonons were observed for GdMn2O5 (x=0) and three additional phonons have been observed with increasing x, marking a total of 21 phonons in YMn2O5 (x=1). A systematic investigation was performed to map out the structural distortion through the lattice vibration and discuss the consequences of frequency shifts in phonon modes. In addition, we have calculated the real part of optical conductivity (σ1(ω)) which reflects the semiconducting nature of Gd1-xYxMn2O5.